PENEGAKAN HUKUM TERHADAP DEBT COLLECTOR YANG MELAKUKAN TINDAK PIDANA DALAM PENARIKAN BARANG ATAU BENDA JAMINAN FIDUSIA DI POLSEK TAMPAN KOTA PEKANBARU - Yudha Chandra Pranata; Mexsasai Indra; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Law enforcement can be interpreted as an effort to implement the law as it should, supervisethe implementation of the law so that there is no violation if there is a violation so there are otherefforts to restore the violated law to be re-enforced. Law enforcement against debt collectors whocommit criminal acts in the withdrawal of fiduciary objects can be done through a legal mechanism,where the debtor feels disadvantaged to be able to report a criminal act committed by a debt collectorto hold accountable.As for the formulation of the problem in this study is how law enforcement against debtcollectors who commit criminal acts in the withdrawal of goods or objects fiduciary collateral andconstraints in the debt collector law enforcement who commit a crime in the withdrawal of goods orfiduciary collateral.The research method used in this case is sociological juridical by direct field survey to obtainprimary data, where this study looks at the continuity between law and society, while the nature of thisresearch is descriptive, namely describing the problems to be studied.Based on the results of the study, it can be seen that law enforcement against debt collectorswho commit criminal acts in the withdrawal of goods or fiduciary collateral objects in the TampbaruPekan Polsek is that the community as a debtor can report any form of crime committed by the debtcollector on the police if the debt collector acts debt collection raises losses to the debtor, whilecriminal acts that can occur include article 369, article 378, article 335 of criminal law, acts of thedebtor who are not cooperative in dealing with debt collectors in general are the cause of theseproblems so that reports on actions a criminal offense that is detrimental to the debtor who mustsurrender the motorized vehicle unit that is used as collateral for the fiduciary and the debtor isunable to avoid the obligation.Constraints in law enforcement against debt collectors who commit criminal acts in thewithdrawal of goods or fiduciary collateral objects can be legal factors where the existence of debtcollectors are not specifically regulated in legislation, making debt collector actions difficult toprocess legally, law enforcement factors or police officers who are weak in responding to criminalacts reported by disadvantaged debtors and community factors which are the most dominant factors ininhibiting law enforcement against debt collectors because debtors are negligent in fulfilling theirachievements in general the community does not know how to do default and avoid collecting debt bydebt collectors.Keywords: Law Enforcement-Debt Collector - Fiduciary Guarantee